2.72. Korzystając z definicji, oblicz pochodną funkcji f w punkcie x 0 a) f(x) = – 2 , x 0 = 3 c) f(x) = 4x ^ 2 + 3x , x 0 =-2 f(x)= 1 x+5 ,x 0 = e) b) f(x) = 3x – 5 , x 0 =-1 d) f(x)=-x^ 2 +5,x 0 =5 x + 1 = 4 f(x)= -2 x-3 ,x 0 =-3 f) d) f)

2.72. Korzystając z definicji, oblicz pochodną funkcji f w punkcie x 0 a) f(x) = – 2 , x 0 = 3 c) f(x) = 4x ^ 2 + 3x , x 0 =-2 f(x)= 1 x+5 ,x 0 = e) b) f(x) = 3x – 5 , x 0 =-1 d) f(x)=-x^ 2 +5,x 0 =5 x + 1 = 4 f(x)= -2 x-3 ,x 0 =-3 f) d) f)

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz